The Role of Stereotypes in the Way Polish Tourists Perceive Romania as a Tourist Destination: A Pilot Study - Michał Żemła; Julia Trojan (Studia Periegetica)
The aim of this article is to highlight how negative stereotypes can shape the image of a destination by analysing Polish tourists’ ideas about Romania. To investigate this problem, the authors analysed verbal and visual associations collected using an online survey involving two groups of respondents: one representing Polish tourists in general (the general public) and the other representing people who were knowledgeable about and interested in Romania (the experts). Representatives of the general public were found to perceive Romania negatively, and their ideas were largely shaped by traditional stereotypes about poverty and the Roma. These stereotypes were not present in the experts’ responses. The results reveal Poles’ poor knowledge of Romania and the need for communication measures in order to reduce the impact of increasingly outdated stereotypes.